Kufu Agama dalam Pernikahan, Peletak Dasar Pendidikan Islam dalam Keluarga Menuju Baiti Jannati - Qurrotul Ainiyah; Luluk Lailatul Mufarida (Halaqa: Islamic Education Journal, 2019)
The similarity and / or balance between prospective brides is known as kufu or kafa'ah, which aims to realize a happy family goal with a heavenly nuance (Baiti Jannati). The materialistic (worldly) mindset also influences humans in determining the criteria for their life partner in marriage. Islam determines that religious considerations will better guarantee the achievement of the goal of marriage, among others, being a happy household with blessings of salih and salihah, because by religion it will be able to educate according to Islamic teachings. The applied research method is Content Analysis, which describes everything related to the subject of systematic research. The results of the study show that if a husband and wife are both sekufu agamaya that is understanding, understanding and practicing Islamic teachings in daily life, it will become educators who have strong religious competence and a good example to his family. In addition to the competence of the educator, it is also supported by methods, material / curriculum and environment.